2018
DOI: 10.1002/mds.109
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy and risk of Parkinson's disease in two large prospective cohorts of men and women

Abstract: Overall, this study suggests limited to no association between appendectomy and Parkinson's disease risk. © 2018 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…In line with these findings it has been shown that a vagotomy or appendectomy early in life are associated with a lower risk to develop PD later in life [8][9][10] [11][12][13][14]. The appendix appears to be the largest source of α-synuclein, whereas the vagus nerve only seems to be the transporter [14,15].…”
Section: Introductionmentioning
confidence: 74%
“…In line with these findings it has been shown that a vagotomy or appendectomy early in life are associated with a lower risk to develop PD later in life [8][9][10] [11][12][13][14]. The appendix appears to be the largest source of α-synuclein, whereas the vagus nerve only seems to be the transporter [14,15].…”
Section: Introductionmentioning
confidence: 74%
“…However, whether the Appendix, as a GI tract lymphoid organ, has an enhanced capacity to generate truncated α-syn amylogenic seeds is unknown. Further studies are required to elucidate the role of Appendix in PD (Marras et al, 2016; Svensson et al, 2016; Yilmaz et al, 2017; Palacios et al, 2018).…”
Section: The Prion-like Mechanism Of Pdmentioning
confidence: 99%
“…diagnostic confirmation procedures in the NHS have been described in prior publications [11]. Briefly, we asked NHS participants to self-report incident PD on biennial questionnaires.…”
Section: Ascertainment Of Pd Cases Pd Identification Andmentioning
confidence: 99%